Effects of targeted therapy on blood gas analysis in pulmonary arterial hypertension – a retrospective analysis. (3rd October 2022) - Kramer, T; Limper, U; Kramer, M; Jordan, J; Tank, J; Hellmich, M; Stehle, R; Baldus, S; Rosenkranz, S
Abstract: Background: In pulmonary arterial hypertension (PAH), there is an excessive respiratory drive, which leads to inefficient ventilation with subsequent hypocapnia. Changes in blood gas analysis (BGA) may correlate with symptom severity and outcome. Data on impact of targeted PAH therapy on BGA are scarce and it remains unclear if these values can be used for risk stratification purposes. Purpose: To assess capillary BGA in PAH at diagnosis and to evaluate the effect of targeted therapy on classical and calculated BGA parameters. Methods: 147 patients (62.3±17.1 years; female/male ratio: 66.7/33.3%) with newly diagnosed PAH were treated with targeted PAH therapy. 12-month follow-up included assessment of capillary blood gases and clinical variables. Patients underwent repeat RHC after 15.9±15.5 months. Results: At diagnosis, both pcO2 (66.8±1.3 mmHg) and pcCO2 (32.7±0.5 mmHg) were slightly reduced. At 12-month follow-up, pcCO2 increased significantly to values within normal range (35.3±0.4 mmHg), while pcO2 showed no significant changes. After using the formula to calculate standard pcO2, baseline values were even lower, but there were significant improvements at 12-month follow-up, also reaching normal values. Changes in pcCO2 and standard pcO2 at diagnosis correlated with hemodynamics and survival at follow-up. Repeated RHC demonstrated significant reductions in mean PAP (48.9±1.2 to 39.9±1.0 mmHg; −18.4%), and PVR (11.3±0.7 to 6.2±0.3 WU; −45.1%), and an increase in cardiac index (2.1±0.04 to 2.6±0.1 ml/min/m 2 ; +23.8%) (all p<0.05). Hemodynamic improvements correlated with improved clinical parameters, including 6-minute walking distance (344±9 to 393±9 m), NTproBNP serum levels (2.163±219 to 772±84 ng/l, both p<0.05) and WHO-FC at 12 months, resulting in improved risk status. Conclusions: Targeted PAH therapy leads to significantly improved cardiopulmonary hemodynamics with subsequent increase in pcCO2, presumably due to less hyperventilation. Changes in pcCO2 and standard pcO2 (but not pcO2) correlate with hemodynamics and survival, potentially serving as non-invasive parameters for risk assessment and therapeutic response. The discrepancy between pcO2 and standard pcO2 at diagnosis suggests that pcO2 is upregulated by the hyperventilatory state. Standard pcO2 represents an easy-to-calculate parameter that can help more accurately identify PAH patients requiring O2 therapy in addition to targeted therapy. Further studies are needed in this context. Funding Acknowledgement: Type of funding sources: None.